Resistance of Halal Tourism: Perceptions, Challenges and Social Impacts - Muharis, Muharis; Taufik, Muhammad; Pribadi, Teguh Iman; Syamsurrijal, Syamsurrijal (CV Insan Kreasi Media, 2024)
Halal tourism is regarded as a rapidly developing segment in the global number of tourists, mainly due to the rising Muslim population. This research seeks to establish the factors that have hindered the growth of halal tourism in Lombok, Indonesia and the local people’s attitude on the subject, the problems that industry stakeholders face; and the culture and social impacts of halal tourism. The study methodology involves using qualitative research with documentation review and analysis as the data collection tool. The study shows that local communities have fears that the development of halal tourism will erode indigenous cultures while industry players highlight issues in meeting the costly halal standards. The findings of this research demonstrate the need to assess local culture compliance in the process of conceptualizing and developing halal tourism and other initiatives to ensure they do not interfere with cultural heritage standards and could foster sustainable tourism.